How do South African Educator's experiences of an online learning course prepare them to adopt inclusive education practices? - Mdlulwa, Ncediwe (Department of Health and Rehabilitation Sciences, 2022)
This research study explored how teachers perceive the potential for online learning opportunities by investigating their experiences of an online course, Education for All: Disability, Diversity, and Inclusion Massive Open Online Course (EFA: DDI MOOC) on teaching children with disabilities. A key underlying concern is that teachers are not sufficiently trained to teach inclusively within their classroom-based environments. The literature reflects that teachers feel that they have not been provided with adequate skills and knowledge to teach students with disabilities and that a massive gap exists in teacher education, which hinders teachers from providing quality education in South Africa. These assessments of the current state of teacher education regarding children with disabilities in this country highlight a considerable need to upskill teachers, particularly those of children with disabilities. One of the proposed responses is to offer flexible online courses such as MOOCs that are open to anyone to enrol. MOOCs are a form of online courses with open enrolment delivered on web-based platforms that can support larger numbers of people. They are free courses that offer unlimited online participation, including technological advancement, peer support as well as collaborative practices. In this study, the EFA: DDI MOOC informs our understanding of how teachers might respond to and value this opportunity. This study thus sought to investigate “How do South African educators' experiences of an online learning course prepare them to adopt inclusive education practices?” Semi-structured interviews were employed as a means of collecting data. A qualitative content analysis was used to analyse and interpret the data set. The researcher was able to ascertain how the MOOC was valued by these participants including acquiring information regarding their level of engagement on the MOOC. The collected data was based on South African educators' experiences of doing the MOOC course and their readiness to implement inclusive education practices for all children with disabilities. The researcher was also interested to ascertain how the online course prepared them to adopt inclusive education practices after completion. This further included establishing how educators perceive MOOCs as being accessible, feasible, and acceptable to their context to develop increased engagement in inclusive teaching practices. The thematic analysis was used to analyse the data from the in-depth interviews. Finally, participants were selected based on the inclusion and exclusion criteria. The interviewees spoke of fundamental changes having occurred after participating in the EFA: DDI MOOC which led to newer understandings of their conceptualisation of inclusion. The benefits to these individual teachers were diverse, with important aspects including their intrinsic motivation, skills development, as well as the desire for continuous professional development. For some there was also an increased willingness to take up the challenge of adopting inclusive education practices as well as becoming agents of change in their communities. The flexible and low-cost MOOC mode was valued as supporting and complementing inclusive teacher education where few other opportunities existed. The overall outcome of the study was that online education (MOOCs) appeared as another important option to consider for the successful implementation of inclusive education practices. Teachers were willing to take up the challenge of adopting inclusive education practices as well as becoming agents of change in their communities. Therefore, the findings signified that MOOCs could aid tremendously towards the goal of achieving inclusive teacher education in South Africa.